The Effect of Variability in the Powder/Liquid Ratio on the Strength of Zinc Phosphate Cement - Jill E. McKenna; Noel J. Ray; Gerald McKenna; Francis M. Burke (International Journal of Dentistry)
Aim. To investigate (a) variability in powder/liquid proportioning and (b) effect of variability on diametral tensile strength (DTS), in a zinc phosphate cement. Statistical analyses (𝛼=0.05) were by Student’s t-test in the case of powder/liquid ratio and one-way ANOVA and Tukey HSD for pair-wise comparisons of mean DTS. The Null hypotheses were that (a) the powder-liquid mixing ratios would not differ from the manufacturer’s recommended ratio (b) DTS of the set cement samples using the extreme powder/liquid ratios would not differ from those made using the recommended ratio. Methodology. 34 dental students dispensed the components according to the manufacturer’s instructions. The maximum and minimum powder/liquid ratios, together with the manufacturer’s recommended ratio, were used to prepare samples for DTS testing. Results. Powder/liquid ratios ranged from 2.386 to 1.018. The mean ratio (1.644) was not significantly different from the recommended value of 1.718 (𝑃=0.189). DTS values for the maximum and minimum ratios were both significantly different from each other (𝑃<0.001) and from the mean value obtained from the recommended ratio (𝑃<0.001). Conclusions. Variability exists in powder/liquid ratio for hand dispensed zinc phosphate cement. This variability can affect the DTS of the set material.